Effect of Nutrition Promoting Program in School on Parental Food Providing Behavior for Primary School Children in Kuanroo Sub-district, Rattaphum District, Songkhla Province - สมบูรณกุล พิจาริน; สุขมาก เพ็ญ (Journal of Health Science of Thailand, 2021)
Parental collaboration in school-based nutrition program help improve child nutritional status. This mix method study aimed to study parental food providing behavior for primary school children after participated in the school nutrition promoting program which has ran under the project called “health promotion in Songkhla food strategy”. Data were collected since December 2018 until January 2019. Sampling was selected by stratified random sampling technique from 2 schools in Kuanroo district, Songkhla Province. Data of 186 parents were collected by food providing behavior questionnaire; and 20 parents were selected by purposive sampling technique to be interviewed about obstacle to follow the nutrition guideline. The study was analyzed with descriptive statistic and content analysis. The study found that most of parent modified the provided food following the recommendation of Department of Health by give their children three meals a day, increase more vegetables and fruits in meal, decrease salty seasonings, snacks, and soft drink. However, most of parents give sweets and sugary drink such as sweet milk and juice. Iron rich foods were still served less than recommendation due to picky eating in children. In conclusion, most of parents improve the food providing behavior but knowledge of labelled-reading and techniques to promoting healthy food to children need to be added in the nutrition promoting program.